Living/controlled supramolecular protein polymerization - Hao Ren; Qianhui Zhang; Kai Wang; Siqi Xu; Wei Liu; Fei Tao; Qian Han; Shuting Miao; Yingying Zhang; Yonggang Liu; Peng Yang (Proceedings of the National Academy of Sciences, 2025)
With the learning from living protein polymerization in nature, achieving living/controlled supramolecular assembly of biopolymers such as proteins in vitro is a longstanding challenge for material design. Herein, we provide a thiol-regulated interfacial protein aggregation (TRIPA) for unfolded protein systems with typical living polymerization features. By triggering globule proteins into the unfolded state through a reversible exchange reaction of disulfide bonds and sulfhydryl agents (R-SH), protein monomers are partially unfolded and assembled at the air–water/solid–water interface (AWI/SWI) through the entropy-driven adsorption and conformation transition. The process could be well repeated over time to form a two-dimensional (2D) nanofilm at the interface by following a pathway of monomer-oligomer-2D assembly. Similar to living polymerization, the film thickness exhibited a linear increase with the assembly conversion ratio of the monomers. With the stepwise addition of native protein into the reaction system, the thickness periodically increased in a linear manner. Such living/controlled supramolecular polymerization (LCSP) of protein at the interface leads to the synthesis of a nanofilm with well-defined flat morphology, ultrahigh modulus, and nano- to macroscale controlled thickness. The resultant protein nanofilm could then attach onto a variety of flexible and rigid material surfaces to produce a stable structural color coating. Compelling evidence in the present work thus underlines a demonstration of LCSP of biopolymers in vitro. It may hold a solid impact by opening a window for living/controlled polymerization of versatile biospecies such as proteins, saccharides, nucleic acids, and cells.